Solitary wave solutions of Fitzhugh-Nagumo-type equations with conformable derivatives - Cevikel, Adem C.; Bekir, Ahmet; Abu Arqub, Omar; Abukhaled, Marwan (FRONTIERS MEDIA SA, 2022)
The Fitzhugh-Nagumo equation is an important non-linear reaction-diffusion equation used to model the transmission of nerve impulses. This equation is used in biology as population genetics; the Fitzhugh-Nagumo equation is also frequently used in circuit theory. In this study, we give solutions to the fractional Fitzhugh-Nagumo (FN) equation, the fractional Newell-Whitehead-Segel (NWS) equation, and the fractional Zeldovich equation. We found the exact solutions of these equations by conformable derivatives. We have obtained the exact solutions within the time-fractional conformable derivative for these equations.
Keywords: exact solutions; conformable derivative; the Fitzhugh-Nagumo equation; solitary wave solution; solitons; Physics